Effect of Different Mulching Materials on Growth and Yield Attributing Characters of Summer Squash in Kanchanpur District - Mahara, Birendra; Bhattarai, Basant Raj; Joshi, Apil; Saud, Ganesh (Journal of Agriculture and Resource Management, 2024)
Mulching in the vegetable crop helps to conserve moisture, regulate temperature, avoid surface compaction, reduce runoff and erosion, improve soil structure, and manage weeds. To study the effect of different mulching materials on growth and yield attributing characters of summer squash, a field experiment was conducted at Kanchanpur district on summer squash during the summer season of 2023. The experiment was laid out in single factor Randomized Complete Block Design (RCBD) design with 4 replications and 5 treatments namely T1: control, T2: Plastic Mulching (silver on black plastic, black on top, silver on bottom), T3: rice straw, T4: sawdust and T5: mustard hulls in an area of 300m2. “F1 Dollar plus” variety was used for the research. Growth and yield characteristics of summer squash were seen better with mulching and provided better results. The effect of different mulching materials on growth and yield attributing characters were found statistically significant except non-significant in a number of leaves at 15DAS. Plant height, number of leaves, and plant spreading were seen highest in treatment T2 and lowest in treatment T1 at 15DAS, 30DAS, 45DAS, and 60DAS. The moisture percentage is retained highest in treatment T3 and the lowest was recorded in treatment T1. The number of fruits per plant, fruit length, yield per plant, and yield were recorded as highest in T2 and lowest in T1. Yield was more than 3 times in treatment T2 and more than double in treatment T3 than in treatment T1. The findings of this research suggest plastic mulching especially silver on black plastic is a better tool for the production of summer squash in the research area compared to non-mulch conditions.